Chemoselective hydration of glycosyl cyanides to C-glycosyl formamides using ruthenium complexes in aqueous media. Issue 44 (28th October 2015) - Misra, Anup Kumar; Bokor, Éva; Kun, Sándor; Bolyog-Nagy, Evelin; Kathó, Ágnes; Joó, Ferenc; Somsák, László
Graphical abstract: Abstract: [RuCl2 (DMSO)4 ] in the presence of N -benzylated 1, 3, 5-triaza-7-phosphaadamantane efficiently catalyzed the hydration of glycosyl cyanides to the corresponding formamide derivatives in water or water– N -methylpyrrolidone solvent mixtures at 105 °C. O -Acetyl, O -benzoyl, and O -benzyl protecting groups, anomeric bromide and azide substituents as well as double bonds were shown to be compatible with these reaction conditions.